2019
DOI: 10.1002/cbf.3427
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy: An evolutionarily conserved process in the maintenance of stem cells and aging

Abstract: Autophagy is an evolutionarily conserved process that degrades and recycles defective organelles, toxic proteins, and various other aggregates on the cytoplasmic surface by sequestering them into autophagosomes which, then, fuse with lysosomes which degrade them. If these aggregates are not cleared, they accumulate and damage the cell resulting in cellular senescence and aging. Stem cells, with their capacity to differentiate, are crucial for tissue homeostasis. In addition to differentiation, the stemness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 60 publications
(124 reference statements)
0
34
0
Order By: Relevance
“…Inhibition of EP300 has been shown to mimic calorific restriction in human and mouse cells (Pietrocola et al 2018); calorific restriction is of course a well-known modifier of lifespan in many species (Austad 1989;Hansen et al 2008;Kapahi et al 2004;Mitchell et al 2010). This protein is also a master regulator of autophagy, which is a pivotal factor in stem cell maintenance and evasion of cellular senescence (Vijayakumar and Cho 2019). circFNDC3B was positively associated with hand grip strength.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of EP300 has been shown to mimic calorific restriction in human and mouse cells (Pietrocola et al 2018); calorific restriction is of course a well-known modifier of lifespan in many species (Austad 1989;Hansen et al 2008;Kapahi et al 2004;Mitchell et al 2010). This protein is also a master regulator of autophagy, which is a pivotal factor in stem cell maintenance and evasion of cellular senescence (Vijayakumar and Cho 2019). circFNDC3B was positively associated with hand grip strength.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is an evolutionary process that recycles cellular components and damaged organelles in response to oxidative stress. In this process, autophagy, in turn, may contribute to reduce oxidative damages by removing ROS byproduct [13] and has a prosurvival role in stem cells, the downregulation of which results in rapid cell death [14]. To date, no study has identified the role of Mst1 in oxidative stressinduced cell apoptosis in MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Mst1 was recently found to act as a switch that simultaneously regulates apoptosis and autophagy in cardiomyocytes [10,11]. Autophagy is an evolutionary process that balances the redox state by scavenging excess intracellular ROS [12] and has a prosurvival role in stem cells, the downregulation of which results in rapid cell death [13]. To date, no study has identi ed the role of [14].…”
Section: Introductionmentioning
confidence: 99%